Przywództwo – kierunek na zarządzanie partycypacyjne: Leadership – the direction of participatory management - Makowiec, Marek; Potocki, Arkadiusz (Management and Administration Journal, 2021)
In this paper the authors take the subject of nature and the importance of leadership in the organization pointing to the desired behaviours and roles that managers should adopt today. Particularly important are the aspects in the context of global economic slowdown and the financial crisis, which had, and still have a great influence on Polish enterprises. One of the instruments of leadership is to communicate, therefore, the results of research on communication in Malopolska companies were subsequently presented. This research was conducted in the years 2008-2011 on a group of 122 managers. Findings and conclusions resulting from the study diagnosed problems and difficulties of communication in an organization and showed how managers are trying to overcome them.